Lithium ion sieve adsorbent and preparation method and application thereof

By synthesizing polyspiropyran in organic solvents and reacting with metal salts to prepare lithium ion sieve adsorbents, the problems of poor stability of lithium ion sieve adsorbents in the prior art, pollution and recycling of recycled waste liquids are solved, and the problem of poor stability of lithium ion sieve adsorbents in the prior art is achieved. Efficient and environmentally friendly lithium ion extraction effect.

CN119455918AActive Publication Date: 2025-02-18ZHIXIN (WUXI) LITHIUM TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411867292.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing lithium ion sieve adsorbents have defects in stability, pollution of recycled waste liquids and difficulty in recycling, making it difficult to effectively extract lithium ions in salt lakes.

Method used

Polyspiropyran was obtained by adding acrylic chloride dropwise to a mixture containing spiropyran and triethylamine in the presence of an organic solvent, and then adding it to the metal salt solution to synthesize with high ion sieving ability. Lithium ion sieve adsorbent.

Benefits of technology

The prepared lithium-ion sieve adsorbent can be synthesized in large quantities at room temperature, with high lithium ion selectivity and adsorption capacity, good circulation performance, and no waste liquid is generated during the desorption process, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455918A_ABST
    Figure CN119455918A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ion sieve adsorbent materials, and discloses a lithium extraction ion sieve adsorbent and a preparation method and application thereof. The method comprises the following steps: in the presence of an organic solvent, dropwise adding acryloyl chloride into a mixed solution I containing spiropyrane and triethylamine to carry out a mixed reaction I to obtain polyspiropyrane; relative to 1g of the mixed solution I; dropwise adding the mixed solution I containing the poly-spiropyrane into a metal salt solution, and carrying out a mixed reaction I to obtain the lithium ion sieve adsorbent; the mixed solution I also contains a ligand for synthesizing MOFs (Metal-Organic Frameworks); the metal salt solution contains at least two of ferric salt, zircon salt and zinc salt. The lithium ion sieve adsorbent prepared by the preparation method provided by the invention can be used for reversibly adsorbing and desorbing adsorbed ions, can be used for efficiently extracting Li < + > from saline water, and also has relatively high selectivity on Na < + >, Mg < 2 + > and Ca < 2 + >; and the lithium ion sieve adsorbent is relatively good in cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion sieve adsorbent materials, and in particular to a lithium extraction ion sieve adsorbent and a preparation method and application thereof. Background Art

[0002] In recent years, due to the rapid development of industries such as glass, ceramics, grease, batteries, refrigerants, and medical treatment, the demand for lithium resources has increased greatly. Nearly 80% of the world's lithium is stored in salt lake brine. The current methods for extracting lithium from brine mainly include: precipitation, evaporation crystallization, solvent extraction, selective membrane separation, ion adsorption, etc. Among them, precipitation and evaporation crystallization are only suitable for extracting lithium from salt lake brine with low Mg / Li, and cause great harm to the environment during operation; while ion adsorption has attracted extensive attention from scientific researchers due to its high recovery rate and high selectivity for lithium ions.

[0003] At present, the main reports on adsorbents for lithium ions in salt lakes are concentrated on ion exchange resins, manganese-based, titanium-based and aluminum-based ion sieves. Ion exchange resins have ion selectivity but the absorption of lithium is low. Aluminum-based adsorbents have improved on this basis, but the adsorption of lithium is still low. Titanium-based and manganese-based ion sieves have high ion selectivity and lithium adsorption, but there is an acid washing process during the synthesis and subsequent desorption process, which leads to the loss of titanium and magnesium ions. There are also problems such as environmental pollution and long adsorbent regeneration time.

[0004] As a new type of functional porous material in recent years, MOFs has a uniform pore structure and adjustable pore size, high porosity and large specific surface area, making it an ideal reagent for selective ion adsorption. At the same time, polyspiropyran (PSP) as a photoisomer can become a zwitterionic state under dark conditions to adsorb anions and cations from salt water, and release the adsorbed anions and cations under light to achieve rapid regeneration of the adsorbent. For example, CN115888667A discloses a method for preparing a photosensitive regenerated lithium adsorbent, which is obtained by heating a metal organic framework MOF and spiropyran SP with an initiator. The photosensitive regenerated lithium ion adsorbent PSP-MOF has high selectivity for lithium and magnesium, and the adsorbed material is desorbed and regenerated by sunlight, showing excellent stability; however, the photosensitive regenerated lithium adsorbent has poor separation effect on lithium and sodium ions, low adsorption capacity for lithium, and difficult adsorbent recovery.

[0005] Therefore, it is urgent to prepare a material with high lithium ion selectivity, large adsorption capacity, easy regeneration, good cycle performance and stable structure for the extraction of lithium ions from salt lakes. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art lithium ion sieve, such as poor stability, regeneration waste liquid pollution and difficulty in recycling.

[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a lithium ion sieve adsorbent, the method comprising:

[0008] (1) in the presence of an organic solvent, acryloyl chloride is added dropwise to a mixed solution I containing spiropyran and triethylamine to perform a mixing reaction I to obtain polyspiropyran;

[0009] Relative to 1 g of the mixed solution I, the dripping flow rate of the acryloyl chloride is 1-3 mL / min;

[0010] (2) adding the mixed solution ⅠⅠ containing the polyspiropyran dropwise into a metal salt solution to carry out a mixing reaction ⅠⅠ, so as to obtain the lithium ion sieve adsorbent; the mixed solution ⅠⅠ also contains a ligand for synthesizing MOFs;

[0011] The metal salt solution contains at least two of iron salt, zirconium salt and zinc salt;

[0012] Relative to 1g of the metal salt solution, the dripping flow rate of the mixed solution ⅠⅠ is 3-10mL / min; the average pore size of the lithium ion sieve adsorbent is 0.6-1.3nm, and the specific surface area is 869-1438m 2 / g.

[0013] The second aspect of the present invention provides a lithium ion sieve adsorbent prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides the use of the lithium ion extraction sieve adsorbent described in the second aspect in the extraction of lithium ions from salt lake brine.

[0015] Through the above technical solution, the present invention has at least the following advantages:

[0016] (1) The method for preparing a lithium ion sieve adsorbent provided by the present invention has a low preparation cost and can rapidly synthesize a lithium ion sieve adsorbent in large quantities at room temperature.

[0017] (2) The lithium ion sieve adsorbent provided by the present invention can efficiently extract Li from brine in a wide pH range. + , to Na + Mg 2+ and Ca 2+ It also has higher selectivity.

[0018] (3) The lithium ion sieve adsorbent provided by the present invention can be used to reversibly adsorb and desorb the adsorbed ions through simple brightness adjustment, with good cycle performance, and no waste liquid is generated during the desorption process, which is environmentally friendly.

[0019] (4) The lithium ion sieve adsorbent provided by the present invention is easy to recover and can be separated from the solution by a magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart of a method for preparing a lithium ion sieve adsorbent according to Example 1 of the present invention;

[0021] Figure 2 Schematic diagram of the adsorption and desorption principle of the lithium ion sieve adsorbent prepared in Example 1 of the present invention;

[0022] Figure 3 Schematic diagram of the recovery of the lithium ion sieve adsorbent prepared in Example 1 of the present invention;

[0023] Figure 4 The lithium ion sieve adsorbent prepared in Example 1 of the present invention is Li in a 1000 ppm solution under different pH conditions. + 、Na + Mg 2+ , Ca 2+ Adsorption capacity graph;

[0024] Figure 5 The lithium ion sieve adsorbent prepared in Example 1 of the present invention is Li in a 1000ppm solution at pH=12. + 、Na + Mg 2+ , Ca 2+ Adsorption kinetics curve;

[0025] Figure 6 The lithium ion sieve adsorbent prepared in Example 1 of the present invention is Li + Desorption kinetics curve;

[0026] Figure 7 The adsorption capacity and ion selectivity curves of the lithium ion sieve adsorbent prepared in Example 1 of the present invention in solutions with different ion concentrations;

[0027] Figure 8 This is the cyclic stability curve of the lithium ion sieve adsorbent prepared in Example 1 of the present invention under continuous operation in a 1000 ppm solution at pH = 12. DETAILED DESCRIPTION

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] In the present invention, MOFs is an organic-inorganic hybrid material, also called a coordination polymer, which is different from both inorganic porous materials and general organic complexes, and has both the rigidity of inorganic materials and the flexibility of organic materials.

[0030] In the present invention, spiropyran is a photochromic dye.

[0031] In the present invention, 2-methylimidazole is an organic compound in the form of white or off-white crystalline powder, which is easily soluble in water, alcohol solutions, soluble in acetone, and poorly soluble in organic solutions such as benzene.

[0032] As mentioned above, the first aspect of the present invention provides a method for preparing a lithium ion sieve adsorbent, the method comprising:

[0033] (1) in the presence of an organic solvent, acryloyl chloride is added dropwise to a mixed solution I containing spiropyran and triethylamine to perform a mixing reaction I to obtain polyspiropyran;

[0034] Relative to 1 g of the mixed solution I, the dripping flow rate of the acryloyl chloride is 1-3 mL / min;

[0035] (2) adding the mixed solution ⅠⅠ containing the polyspiropyran dropwise into a metal salt solution to carry out a mixing reaction ⅠⅠ, so as to obtain the lithium ion sieve adsorbent; the mixed solution ⅠⅠ also contains a ligand for synthesizing MOFs;

[0036] The metal salt solution contains at least two of iron salt, zirconium salt and zinc salt;

[0037] Relative to 1g of the metal salt solution, the dripping flow rate of the mixed solution ⅠⅠ is 3-10mL / min; the average pore size of the lithium ion sieve adsorbent is 0.6-1.3nm, and the specific surface area is 869-1438m 2 / g.

[0038] The inventors of the present invention have discovered that by using spiropyran, ligands for synthesizing MOFs and metal salts as raw materials and controlling the process steps and reaction parameters, a lithium ion sieving adsorbent can be successfully prepared. The adsorbent has a high ion sieving ability and has a large pore cavity that can fix the photosensitive adsorbent therein, so that the functionalized MOFs have good stability during actual use.

[0039] Preferably, the ligand used to synthesize MOFs is 2-methylimidazole, and the metal salt solution contains zinc salt and iron salt.

[0040] Preferably, the molar ratio of the zinc salt to the iron salt is 1:0.1-0.6.

[0041] Preferably, the zinc salt is zinc acetate; and the iron salt is ferrous chloride.

[0042] Preferably, the ligand used to synthesize MOFs is terephthalic acid, and the metal salt solution contains zirconium salt and iron salt.

[0043] Preferably, the molar ratio of the zirconium salt to the iron salt is 1:0.5-1.

[0044] Preferably, the zirconium salt is zirconium chloride; and the iron salt is ferrous chloride.

[0045] Preferably, the ligand used to synthesize MOFs is trimesic acid, and the metal salt solution contains zirconium salt and iron salt.

[0046] Preferably, the molar ratio of the zirconium salt to the iron salt is 1:0.1-0.4.

[0047] Preferably, the zirconium salt is zirconium chloride; and the iron salt is ferrous chloride.

[0048] Preferably, in step (1), the molar ratio of the spiropyran to the triethylamine is 1:7-12.

[0049] Preferably, in step (1), the mixed reaction I comprises a first mixed reaction I and a second mixed reaction I carried out sequentially, wherein the conditions of the first mixed reaction I include: temperature of -2 to 10°C, and time of 0.5-3h; the conditions of the second mixed reaction I include: temperature of 18-22°C, and time of 1-3h.

[0050] Preferably, in step (1), the organic solvent is dichloromethane.

[0051] Preferably, the method further comprises: in step (1), subjecting the product obtained from the mixed reaction I to impurity removal treatment to obtain the polyspiropyran.

[0052] More preferably, the impurity removal treatment comprises filtering, washing and extracting performed in sequence.

[0053] More preferably, the extraction is carried out using a basic alumina column.

[0054] Preferably, in step (2), in the mixed solution ⅠⅠ, the molar ratio of the polyspiropyran to the ligand for synthesizing MOFs is 0.3-0.8:1.

[0055] Preferably, in step (2), the conditions of the mixed reaction Ⅱ include: temperature of 25-50°C and time of 0.5-10h.

[0056] Preferably, the method further comprises: in step (2), washing the product obtained from the mixed reaction Ⅱ to obtain the lithium ion sieve adsorbent.

[0057] More preferably, the solvent used for the washing is selected from any one of methanol, ethanol, N,N-dimethylformamide and water.

[0058] As mentioned above, the second aspect of the present invention provides a lithium ion sieve adsorbent prepared by the method described in the first aspect.

[0059] As mentioned above, the third aspect of the present invention provides the use of the lithium ion extraction sieve adsorbent described in the second aspect in the extraction of lithium ions from salt lake brine.

[0060] The present invention will be described in detail below by way of examples.

[0061] In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through conventional commercial channels. In particular, unless otherwise specified, the reagents used are all commercially available analytically pure products.

[0062] Acryloyl chloride was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a CAS number of 814-68-6 and a purity of 96%.

[0063] Spiropyran was purchased from Beijing Huawei Ruike Chemical Co., Ltd. with a purity of 97%.

[0064] 2-Methylimidazole was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a CAS number of 693-98-1 and a purity of 98%.

[0065] Example 1

[0066] (1) In a 250 mL round-bottom flask, in the presence of 75 mL of an organic solvent (dichloromethane), acryloyl chloride was added dropwise to a mixed solution I containing spiropyran and triethylamine and stirred to sequentially perform a first mixed reaction I (temperature of 0° C., time of 1 h) and a second mixed reaction I (temperature of 20° C., time of 2 h);

[0067] The product obtained from the second mixed reaction I was filtered to remove salt precipitation, diluted with 50 mL of dichloromethane, and then washed 3 times with 50 mL of saturated NaHCO3 solution and once with 50 mL of brine;

[0068] The washed product was dried using MgSO4, added with 15 mL of methanol and extracted through a basic alumina column;

[0069] Finally, the remaining solvent was evaporated by a rotary evaporator at 40° C. and 90-100 kPa to obtain the polyspiropyran PSP.

[0070] (2) adding two or more metal salts to 5 mL of water and stirring to obtain a metal salt solution;

[0071] The aforementioned polyspiropyran and the ligand for synthesizing MOFs are added into 5 mL of water and stirred evenly to obtain a mixed solution containing polyspiropyran and the ligand for synthesizing MOFs ⅠⅠ;

[0072] The mixed solution ⅠⅠ containing polyspiropyran was added dropwise to the metal salt solution for mixing reaction ⅠⅠ (temperature was 25° C., time was 0.5 h), and the product obtained by mixing reaction ⅠⅠ was washed 3 times with deionized water to obtain a lithium ion sieve adsorbent.

[0073] The present invention is exemplarily Figure 1 A preparation flow chart of the lithium ion sieve adsorbent prepared in this embodiment is provided;

[0074] The raw material ratio and process conditions of this embodiment are shown in Table 1.

[0075] Unless otherwise specified, Examples 2 and 3 are carried out using a method similar to that of Example 1, except that different raw material ratios and process conditions are used. For details, see Table 1.

[0076] Table 1 (the amount of mixed solution I is 1g, the amount of metal salt solution is 1g)

[0077]

[0078]

[0079] Example 4

[0080] This example is carried out using a method similar to that of Example 1, except that in this example, the ligand used to synthesize MOFs is 2-methylimidazole, and the metal salt is a combination of 1 mol of nickel acetate and 0.5 mol of cupric chloride.

[0081] The obtained lithium ion sieve adsorbent has an average pore size of 1.12nm and a specific surface area of ​​1326m 2 / g.

[0082] Example 5

[0083] This example is carried out using a method similar to that of Example 3, except that in this example, the ligand used to synthesize MOFs is trimesic acid, and the metal salt is a combination of 1 mol of zinc acetate and 0.8 mol of cuprous chloride.

[0084] The lithium ion sieve adsorbent was obtained, with an average pore size of 0.84 nm and a specific surface area of ​​1035 m 2 / g.

[0085] Comparative Example 1

[0086] This comparative example was carried out in a similar manner to Example 1, except that the amount of mixed solution I in this comparative example was kept unchanged and the dripping flow rate of acryloyl chloride was adjusted to 5 mL / min.

[0087] The lithium ion sieve adsorbent was obtained, with an average pore size of 1.11 nm and a specific surface area of ​​1027 m 2 / g.

[0088] Comparative Example 2

[0089] This comparative example was carried out in a similar manner to Example 1, except that the amount of the metal salt solution in this comparative example was kept unchanged and the dripping flow rate of the mixed solution ⅠⅠ was adjusted to 1 mL / min.

[0090] The obtained lithium ion sieve adsorbent has an average pore size of 1.06nm and a specific surface area of ​​1236m 2 / g.

[0091] Test Case

[0092] The performance of the lithium ion sieve adsorbent prepared in the above examples was tested, including the adsorbent's performance on Li + 、Na + Mg 2+ , Ca 2+ The adsorption capacity of the adsorbent for Li at pH = 12 + 、Na + Mg 2+ , Ca 2+ The adsorption kinetics test, desorption kinetics test of the adsorbent in LiCl solution, adsorption capacity and ion selectivity test of the adsorbent in solutions with different ion concentrations, and cyclic stability test of the adsorbent during continuous operation.

[0093] Some test results are shown in Table 2.

[0094] The ion concentration is analyzed by ICP-AES; the adsorption amount Q is calculated by the ion concentration in the solution before and after ICP-AES analysis, and the formula is: Q t =(C0-C t )×V / (m×M);

[0095] In the formula, Q tis the ion adsorption amount at any time t, C0 is the initial salt solution ion concentration, unit is mg / L; C t is the ion concentration of the salt solution at any time t, in mg / L; m is the mass of the adsorbent, in g; V is the volume of the salt solution, in L; M is the relative molecular mass of the metal ion.

[0096] Table 2

[0097]

[0098] The present invention is exemplarily Figure 2 A schematic diagram of the adsorption and desorption principle of the lithium ion sieve adsorbent prepared in Example 1 is provided. Figure 2 It can be seen that under dark conditions, the lithium ion sieve adsorbent can be used as a water-absorbing material to quickly absorb Ca 2+ Mg 2+ Screening, Li + and Na + After the adsorption is completed, visible light is added, and the material is transformed into a hydrophobic material due to its hydrophobic properties (the hydrophobic angle changes from 56° to 107°), and desorption and regeneration begin.

[0099] The present invention is exemplarily Figure 3 A schematic diagram of the recovery of the lithium ion sieve adsorbent prepared in Example 1 is provided. Figure 3 It can be seen that the lithium ion sieve adsorbent has a strong affinity for Ca under dark conditions. 2+ Mg 2+ , Li + and Na + After adsorption, it can be transferred to visible light and the adsorbent can be adsorbed by a magnet, thereby achieving rapid separation, desorption and regeneration, avoiding the use of acidic regeneration eluents and causing environmental pollution.

[0100] The present invention is exemplarily Figure 4 The lithium ion sieve adsorbent prepared in Example 1 is provided for Li under different pH conditions in a 1000 ppm solution. + 、Na + Mg 2+ , Ca 2+ Adsorption capacity diagram. Figure 4 It can be seen that with the increase of pH, the adsorption capacity of the adsorbent for cations in the salt solution gradually increases. When pH = 12, the lithium ion sieve adsorbent has the largest cation adsorption capacity, and its adsorption capacity remains basically unchanged as the alkalinity of the salt solution continues to increase.

[0101] The present invention is exemplarily Figure 5 The lithium ion sieve adsorbent prepared in Example 1 is provided for Li in a 1000 ppm solution at pH = 12.+ 、Na + Mg 2+ , Ca 2+ Adsorption kinetics curve. Figure 5 It can be seen that Na + , Li + After 40 min, the adsorption reached saturation, and Ca 2+ Mg 2+ Adsorption saturation was reached after 10 min.

[0102] The present invention is exemplarily Figure 6 The lithium ion sieve adsorbent prepared in Example 1 is provided for Li + Desorption kinetics curve. Figure 6 It can be seen that Li + Complete desorption can be achieved after 8 minutes.

[0103] The present invention is exemplarily Figure 7 The adsorption capacity and ion selectivity curves of the lithium ion sieve adsorbent prepared in Example 1 in solutions with different ion concentrations are provided. Figure 7 It can be seen that as the salt concentration gradually increases, the adsorbent + 、Na + Mg 2+ , Ca 2+ The adsorption capacity of the adsorbent increases accordingly. When the ion concentration in the solution exceeds 10000ppm, the adsorption capacity remains basically unchanged. When the ion concentration is 5000ppm, the adsorbent has the largest Li + Selectivity, continue to increase the salt concentration, the ion selectivity remains basically unchanged.

[0104] The present invention is exemplarily Figure 8 The cyclic stability curve of the lithium ion sieve adsorbent prepared in Example 1 under continuous operation in a 1000 ppm solution at pH = 12 is provided. Figure 8 It can be seen that after multiple adsorption-desorption tests, the adsorption capacity of the lithium ion sieve adsorbent did not decrease significantly.

[0105] It can be seen from the above results that the lithium ion sieve adsorbent prepared by the method for preparing a lithium ion sieve adsorbent provided by the present invention can reversibly adsorb and desorb the adsorbed ions, and can efficiently extract Li from brine. + , to Na + Mg 2+ and Ca 2+ It also has high selectivity; and the lithium ion sieve adsorbent has good cycle performance.

[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a lithium ion sieve adsorbent, characterized in that: The method includes: (1) in the presence of an organic solvent, acryloyl chloride is added dropwise to a mixed solution I containing spiropyran and triethylamine to perform a mixing reaction I to obtain polyspiropyran; Relative to 1 g of the mixed solution I, the dripping flow rate of the acryloyl chloride is 1-3 mL / min; (2) adding the mixed solution ⅠⅠ containing the polyspiropyran dropwise into a metal salt solution to carry out a mixing reaction ⅠⅠ, so as to obtain the lithium ion sieve adsorbent; the mixed solution ⅠⅠ also contains a ligand for synthesizing MOFs; The metal salt solution contains at least two of iron salt, zirconium salt and zinc salt; Relative to 1g of the metal salt solution, the dripping flow rate of the mixed solution ⅠⅠ is 3-10mL / min; the average pore size of the lithium ion sieve adsorbent is 0.6-1.3nm, and the specific surface area is 869-1438m 2 / g.

2. The method according to claim 1, wherein: The ligand used to synthesize MOFs is 2-methylimidazole, and the metal salt solution contains zinc salt and iron salt; Preferably, the molar ratio of the zinc salt to the iron salt is 1:0.1-0.6; Preferably, the zinc salt is zinc acetate; and the iron salt is ferrous chloride.

3. The method according to claim 1, wherein: The ligand used to synthesize MOFs is terephthalic acid, and the metal salt solution contains zirconium salt and iron salt; Preferably, the molar ratio of the zirconium salt to the iron salt is 1:0.5-1; Preferably, the zirconium salt is zirconium chloride; and the iron salt is ferrous chloride.

4. The method according to claim 1, wherein: The ligand used to synthesize MOFs is trimesic acid, and the metal salt solution contains zirconium salt and iron salt; Preferably, the molar ratio of the zirconium salt to the iron salt is 1:0.1-0.4; Preferably, the zirconium salt is zirconium chloride; and the iron salt is ferrous chloride.

5. The method according to any one of claims 1 to 4, wherein: In step (1), the molar ratio of the spiropyran to the triethylamine is 1:7-12.

6. The method according to any one of claims 1 to 4, wherein: In step (1), the mixed reaction I includes a first mixed reaction I and a second mixed reaction I carried out in sequence, wherein the conditions of the first mixed reaction I include: temperature of -2 to 10°C, time of 0.5-3h; the conditions of the second mixed reaction I include: temperature of 18-22°C, time of 1-3h.

7. The method according to any one of claims 1 to 4, wherein: In step (2), in the mixed solution ⅠⅠ, the molar ratio of the polyspiropyran to the ligand for synthesizing MOFs is 0.3-0.8:

1.

8. The method according to any one of claims 1 to 4, wherein: In step (2), the conditions of the mixed reaction Ⅱ include: temperature of 25-50°C and time of 0.5-10h.

9. A lithium ion sieve adsorbent prepared by the method according to any one of claims 1 to 8.

10. Use of the lithium ion extraction sieve adsorbent according to claim 9 in extracting lithium ions from salt lake brine.

Citation Information

Patent Citations

  • Preparation method of lithium ion imprinted PVDF membrane based on MOFs

    CN115445448A

  • Photosensitive regenerated lithium adsorbent and preparation method thereof

    CN115888667A

  • Metal-organic framework loaded spiropyrane photochromic dual material and preparation method thereof

    CN116554868A

  • Method for recovering adsorption material having light and thermal responsibility and soluble material

    JP2005103534A